SCART sequential lattice spatial fractionated radiotherapy combined with chemotherapy for recurrent ovarian cancer with bulky bone metastasis: a case report - Li, Yuan; Han, Liangfu; Yan, Weisi; Yang, Jun (Frontiers in Oncology, 2026)
BackgroundBone metastasis from ovarian cancer is relatively rare, and the treatment of giant bone metastatic lesions poses significant clinical challenges. SCART (Stereotactic Centralized Ablative Radiation Therapy) and Lattice technique, as emerging spatial fractionated precision radiotherapy technologies, have shown unique advantages in treating bulky tumor lesions. This case report explores the potential immunomodulatory effects of spatial fractionated radiotherapy in enhancing tumor antigenicity and chemotherapy sensitivity in recurrent, drug-resistant, multi-line treated cancer patients.Case presentationWe report a 56-year-old female patient with ovarian cancer recurrence and multiple metastases 7 years post-surgery. CT examination revealed a big right iliac bone metastatic lesion (89×78×58mm) with surrounding soft tissue invasion. After limited response to chemotherapy and bevacizumab, the patient underwent sequential SCART, SBRT, and Lattice radiotherapy for her right iliac and surrounding invasive soft tissue metastases. Substantial local tumor regression was achieved without severe acute toxicity.MethodsThe initial radiotherapy consisted of SCART followed by SBRT: STV 54 Gy/3 fractions, PGTV 15 Gy/3 fractions, then SBRT PGTV 25 Gy/5 fractions. Stage II treatment used Lattice radiotherapy: VTV 45 Gy/3 fractions and PGTV 9 Gy/3 fractions.ResultsThe patient’s pain symptoms were significantly relieved, with good tolerance during treatment and no severe adverse reactions. According to RECIST 1.1 evaluation criteria, the baseline GTV was 399.0cc, decreased to 308.0cc after SCART +SBRT, and further reduced to 136.1cc at 6-month follow-up MRI after Lattice radiotherapy. The diameter decreased by approximately 30.1% compared to baseline, achieving partial response.ConclusionThe combination of SCART and Lattice techniques offers a promising strategy for managing bulky tumor, particularly suitable for cases with less-responsive to conventional therapy. This technique ensures safe dose at target margins while increasing dose to “cold tumor” areas, offering new clinical options. This approach safely escalates intratumoral dose while protecting normal tissue and may enhance immunogenic and cytotoxic responses. Sequential spatial fractionation techniques appear feasible, with controllable short-term safety and favorable tolerance.